Different Methods of Authentication for Mobile Banking - Nosrati , Leili; Nosratri, Laleh (International Journal of Membrane Science and Technology, 2023)
Online banking authentication has been recognized as a key factor in the security of online banking. nowadays, different methods have been developed for online banking validation which cause problems from hacker attacks and Internet theft. Our research showed that biometrics is appropriate options for dealing with these issues. In this article, different authentication protocols for online banking have been compered.